On the Shoulders of Giants: Benefits of Participating in a Dialogic Professional Development Program for In-Service Teachers - Rodriguez, Jose A.; Condom-Bosch, Jose Luis; Ruiz, Laura; Oliver, Esther (Frontiers in Psychology, 2020)
This study explores the impact of a seminar on self-efficacy and argumentative skills on teachers’ professional development. In this seminar, called “On the Shoulders of Giants,” a group of teachers meet once a month. They debate scientific readings to critically discuss educational theory, which transforms their everyday practices in the school. A survey using a questionnaire was conducted to collect the data. The results show that teachers’ involvement in dialogic-based training positively impacts their ability to address current school problems and that the teachers transfer their new knowledge to their work. The effectiveness of the teachers’ practices increases and, consequently, their students’ learning also improves.